Comparison of Efficacy of Optical Coherence Tomography, Angiography in patients suffering from true or Pseudo-Optic Disc Swelling - Nesr Farooq, Syed Abdullah Mazhar, Baber Attique Malik, Saad Muhammad Iqbal, Khurram Nafees, Bushra Rehman, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Optical Coherence Tomography Angiography (OCTA) is a non-invasive, detailed visualization of the retinal and choroidal vascular layers, allowing for accurate detection of abnormalities. Objective: To compare the efficacy of optical coherence tomography angiography in patients suffering from true or pseudo optic disc swelling. Study Design: Comparative study Place and Duration of Study: Department of Ophthalmology, Shalamar Medical & Dental College Lahore from 1st January 2023 to 31st October 2023. Methodology: There were total 60 (80 eyes) ass cases compared with 50 (50 eyes) as controls. In the control group one healthy eye of each participant was enrolled in the study for comparison. Patients suffering from ONHD eyes, papilledema or with NAION were included in this study. All patients underwent a detailed ophthalmological examination involving measurement of best corrected visual-acuity (BCVA), light sensitivity pupillary reaction of pupillary defect identification. Photographic images of the dilated fundus were taken through Topcon fundus camera. The patients suffering from the ODS were further divided into three sub groups where in G1A was those patients suffering from papilledema (n=20) while G1B were ONHD (n=20) and G1 C were NAION (n=20).A three-dimensional artifact eliminator (PAR) algorithm was installed in the software, for improving the image quality. Pupillary dilation was achieved in each patient followed by peripapillary RNFL imaging. Disc boundaries were categorized, and false identifications were corrected by adjusting disc marginal-points and RNFL was recalculated/analyzed. Results: In the mean age of the patients was 35.54±12.5 years and controls was 42.5 ± 15.5 years. There were more females than males in the study except in NAION patients. The NAION has the highest values of mean peripapillary-RNFL thickness in eyes. Papilledema had second highest values while control eyes had lowest mean peripapillary RNFL thickness. The sectoral mean thickness of peripapillary RNFL were also high in all patient group except in the healthy controls with a p value as <0.001. The densities of the vessels were measured post exclusion of large vessels. The maximum value for vessel density of peripapillary was observed in ONHD followed by healthy controls and NAION respectively. There was no variance in mean density of peripapillary of ONHD and healthy controls (p value 0.332). Within peripapillary sectors the values of vessel density in nasal region presented no significant difference than other groups while in comparison to healthy controls a significant decrease in vessel density of eyes with the papilledema at temporal and supertemporal regions. Conclusion: Radial peripapillary capillary (RPC) density is predisposed during ONHD condition as well as in NAION and papilledema. There is a reduction in density of vessel parameters in true disc-edema with emphasis of future more detail study required to analyses Keywords: Efficacy, Optical choherence tomography, Angiography Pseduo-optic disc swelling